Consumer preferences and purchasing rationales for wine: a multivariate data analysis - Carla Ferreira; João Rebelo; Lina Lourenço-Gomes; Elisete Correia; Philippe Baumert; Christine Plumejeaud (New Medit, 2020)
The wine market is very heterogeneous and complex, being the knowledge of the behaviour and attitudes of consumers a key tool to design efficient marketing plans, namely in countries that are traditionally wine producers and consumers, such as Portugal. In this country, Port wine is an economic and cultural icon, but, in the last decade, total sales have been decreasing. Despite this trend the domestic consumption has been gaining relevance and therefore a focus to reverse the negative cycle of total sales. The main goal of this paper is to analyse the profile and behaviour of domestic Port wine consumers, identifying homogeneous market segments. For this purpose, an online survey was applied and random sample of 678 Portuguese Port wine consumers was collected. Using multivariate statistical techniques, three profiles of purchasers/consumers emerged: experienced, less experienced and inexperienced consumers. This segmentation shows that Port wine consumers can be grouped according to their involvement with the product, consumption occasion and price they are willing to pay. In addition to the academic contribution of wine market segmentation, the paper provides useful insights to be used in designing marketing plans, both by institutional stakeholders and wineries.